PENGEMBANGAN MEDIA PAPINMAT (PAPAN PINTAR MATEMATIKA) PADA MATERI BANGUN RUANG KELAS IV SDPENGEMBANGAN MEDIA PAPINMAT (PAPAN PINTAR MATEMATIKA) PADA MATERI BANGUN RUANG KELAS IV SD - Komang Wira Ardika; I Komang Wahyu Wiguna; Putu Yulia Angga Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics learning requires media that can present concepts concretely and be easily used/practical. Based on these needs, this study developed PAPINMAT (Smart Math Board) media for Grade IV elementary school. This study aims to produce PAPINMAT media, determine the product validity level, and analyze its practicality. This study employs Research and Development (R&D) methodology utilizing the ADDIE development framework modified up to the implementation phase. The research subjects comprised subject matter experts, media experts, language experts, 3 elementary school teachers, and 18 Grade IV students from Sukasada Cluster III. Data collection techniques included observation, interviews, documentation, and structured questionnaires. Results revealed that PAPINMAT was successfully developed as a teaching aid. Product validity testing achieved high mean scores: 92% from subject matter experts, 98% from media experts, and 94% from language experts, all residing in the